2017
DOI: 10.1083/jcb.201705214
|View full text |Cite
|
Sign up to set email alerts
|

The TRAPPIII complex activates the GTPase Ypt1 (Rab1) in the secretory pathway

Abstract: The TRAPP complexes are nucleotide exchange factors that activate Rab GTPases, and four different versions of TRAPP have been reported. Thomas et al. show that only two versions of TRAPP are detectable in normal cells and demonstrate that the TRAPPIII complex regulates Golgi trafficking in addition to its established role in autophagy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

15
140
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 69 publications
(160 citation statements)
references
References 66 publications
15
140
1
Order By: Relevance
“…To test this, we performed time-lapse imaging experiments. Consistent with previous studies, mNG-Ypt1 levels peaked approximately 20 seconds upstream of Sec7, correlating with TRAPPIII-mediated nucleotide exchange (Figure 5C and D; McDonold and Fromme, 2014; Thomas et al, 2018). mNG-Ypt1 HVD32 also accumulated upstream of Sec7, but recruitment of the chimera peaked significantly later.…”
Section: Resultssupporting
confidence: 91%
See 4 more Smart Citations
“…To test this, we performed time-lapse imaging experiments. Consistent with previous studies, mNG-Ypt1 levels peaked approximately 20 seconds upstream of Sec7, correlating with TRAPPIII-mediated nucleotide exchange (Figure 5C and D; McDonold and Fromme, 2014; Thomas et al, 2018). mNG-Ypt1 HVD32 also accumulated upstream of Sec7, but recruitment of the chimera peaked significantly later.…”
Section: Resultssupporting
confidence: 91%
“…In contrast to TRAPPII, TRAPPIII can associate directly with TGN membranes in the absence of other recruiters (Figure S1B), and we confirmed that TRAPPIII activated Ypt1, but not Ypt32, in the presence of TGN liposomes (Figure 1E; Thomas et al, 2018). Taken together these data indicate that, under physiological conditions, the two TRAPP complexes display distinct Rab substrate specificities.…”
Section: Resultssupporting
confidence: 69%
See 3 more Smart Citations